A Morphosyntactic Investigation of Functional Categories in English and Ịzọn (2012)
Existing studies on Ịzọn language have concentrated on unilingual application of traditional grammar in constructing well-formed sentences, thereby neglecting critical descriptions of the ways morphosyntactic features ensure the derivation of convergent structures. A contrastive examination of English, (a standard for universal grammar analysis) and Ịzọn languages can properly characterise these syntactically significant features. This work, therefore, investigates the morphosyntactic features in English and Ịzọn languages with a view to identifying and describing the morphosyntactic features that make the structures of the two languages converge. The study adopts Chomsky‟s Minimalist Program, which emphasises checking of morphological features. The research is based on Standard English and the Kolokuma dialect of Ịzọn, used in education and the media, and is mutually intelligible with other dialects. Data on English were collected from various books on English grammar and those on Ịzọn were collected from native speakers in Kolokuma and Opokuma clans in Bayelsa State where the dialect is spoken, and complemented with the researcher‟s native-speaker‟s introspective data. Since the study is competence-based, completely grammatical structures from each language were used for the analysis. Clausal and phrasal syntactic structures of English and Ịzọn languages were comparatively analysed based on the feature-checking processes of the Minimalist Program to identify shared and idiosyncratic features. Universal features common to both languages include phrases, clauses, syntactic heads and wh-fronting. However, English and Ịzọn opt for different head parameters. Heads in English precede their complements while heads in Ịzọn follow their complements. Although Nominative Case licensing occurs in Spec-head structures in both languages, Accusative Case is licensed in head–complement relationship in English and complement-head structure in Ịzọn. Both English and Ịzọn permit wh-fronting at Spec-CP, but Ịzọn wh-expressions obligatorily co-occur with focus particles kị or kọ, which are functional elements that licence wh-elements. Whereas English constructs relative clauses with overt and interpretable complementizers such as „who‟, which precede their complement clauses, Ịzọn constructs relative clauses without overt interpretable wh-expressions except an overt amẹẹ (that) which follows its complement clause. Agreement and Case features are intrinsic in determiners and pronouns in both languages. Whereas referential determiners in English have referential features only, some referential determiners in Ịzọn also have gender agreement features. English verbs have interpretable number agreement feature, but Ịzọn verbs lack this: the verb in Ịzọn does not inflect for number and is uninterpretable. Therefore, movement of the verb for checking of +N feature is overt and occurs before Spell-Out in English, but it is covert and occurs after Spell-Out in Ịzọn. Nevertheless, Ịzọn permits the projection of multiple XPs within a single DP in which two determiners participate in DP-internal Agreement relations with the noun. Phrasal and clausal structures, heads, Case and wh-movement are common features of English and Ịzọn languages. The interpretability of morphosyntactic features, head directionality and nature of wh-movement licensing constitute peripheral features to the two languages. This study provides a systemic characterization of the interface of functional morphological features and syntactic derivations in English and Ịzọn languages.